Using Dicamba in Dicamba-Tolerant Crops - Jason Ferrell; Pratap Devkota (EDIS)
This 3-page publication discusses the following considerations regarding the use of dicamba in dicamba-tolerant crops: dicamba product selection, tank-mix products, buffer requirements, nozzle selection, boom height, wind speed, and ground speed. Written by J. A. Ferrell and P. Devkota, and published by the UF/IFAS Agronomy Department, revised June 2020.